Do Thai parents really know about the sexual risk taking of their children? A qualitative study in Bangkok - Fongkaew W. (2014)
This qualitative study explores the perceptions of parents and adolescents toward sexual risk-taking behaviors. In-depth interviews were conducted with 30 parents and 30 adolescents (aged 13-14years) in Bangkok, and were analyzed by using coding and thematic analysis. The results showed that although parents generally believed that Thai teens begin to have sex at an early age and engage in sexual risk-taking behaviors, they trusted that their teens would follow parental guidance and rules and not engage in sexual activity at this age. Most of the Thai teens reported that their parents were not really aware of their sexual behaviors because of their tendency to keep their sexual stories secret for fear of being scolded, blamed, and punished. The teens also reported that they wanted their parents to listen, give them warmth and more freedom, and be more in touch with their activities. Parents expressed their need for knowledge and skills so that they could help guide their adolescent children to avoid sexual risk-taking behaviors. A family intervention specifically aimed at empowering Thai urban parents is needed. © 2012 Wiley Publishing Asia Pty Ltd.